Effects of fluvastatin on structure and function of resistant vessels in spontaneously hypertensive rats. - Lin Zhi-hong; Xie Liang-di; Wu Ke-gui; Wang Hua-jun; Xu Shang-sheng (Acta Pharmacologica Sinica, 2016)
AIM: To evaluate the effects of fluvastatin, a hydroxymethylglutaryl-CoA (HMG-CoA) reductase inhibitor, on the alterations of structure and function of resistant vessels in spontaneously hypertensive rats (SHR). METHODS: Eight-week-old male SHR were given fluvastatin 20 mg.kg-1.d-1 by gavage. Rats were decapitated at 16 wk. Wall-to-lumen area ratios (W/L) of thoracic aorta and mesenteric arteries (3rd grade branch) were assessed by morphometric assay. The effects of fluvastatin on vascular reactivity to sodium nitroprusside (SNP) and norepinephrine (NE), were studied with rings of thoracic aorta and mesenteric arteries isolated from rats. RESULTS: After 8 wk of treatment, histological examination showed that the wall-to-lumen area ratio was lower in SHRflu than that in SHR (0.44 +/- 0.09 vs 0.79 +/- 0.09, P < 0.05). EC50 of vasodilation response was much lower in SHRflu than that in SHR [(4.9 vs 190) pmol.L-1, P < 0.05], while EC50 of mesenteric artery rings from SHRflu was somewhat lower than that of SHR [(0.02 vs 0.04) nmol.L-1, P > 0.05]. In both aortic and mesenteric artery rings, EC50 of vasoconstriction in response to NE from SHRflu was higher than that of SHR [thoracic aorta: (0.20 vs 0.02) nmol.L-1, P < 0.05; mesentric arteries: (1.46 vs 0.72) nmol.L-1, P < 0.05]. CONCLUSION: Short-term treatment with fluvastatin ameliorated the vasomotoricity of resistant vessels, enhanced the sensitivity to vasodilator and depressed the sensitivity to vasoconstrictor; fluvastatin also attenuated the resistant vascular hypertrophy during the development of hypertension in SHR.